The hunter's choice: faunal remains from Maqonqo Shelter, South Africa - Plug, I. (Southern African Humanities, 2021)
The faunal remains from Maqonqo Shelter suggest that it was one of the most important sites in the social and ritual life of hunter-gatherer communities of the Thukela Basin during the early and mid-Holocene. The volume of the faunal assemblage and the variety of species represented, exceed those from other sites in the area. The sample contains, in unusual abundance, skeletal elements of species traditionally associated with ritual activities, such as the aardvark and pangolin. The sample also contains a number of species not endemic to the region, although minor environmental changes could have brought some within range of Maqonqo. However, the combination of non-endemics with divergent habitat requirements, exclude the possibility that climate change alone was responsible for their presence; hunting expeditions, social contacts, trade and/or gift exchange networks could have contributed. To cite this paper: Plug, I. 1996. The hunter's choice: faunal remains from Maqonqo Shelter, South Africa. Natal Museum Journal of Humanities 8: 41-52.